Building Bridges Between Academia, Politics, and Media - Kühnhardt, Ludger. author. aut Link
XXXIX, 1187 p. 328 illus., 2 illus. in color.
Keywords: Ludger Kühnhardt, a globally active political scientist, consultant, and publicist, provides vivid and personal insights into the people and sources that have shaped him, the thought paths he has followed, and the impulses his work in research and teaching has triggered over decades. A biographical workshop report of high authenticity that brings together what often appears unconnected in the midst of professional everyday life. Insights that were ahead of their time are repeatedly illuminated from different perspectives, and findings that have remained timelessly relevant are recalled. A vividly written work biography about the inner driving forces and external contexts of a cosmopolitan public intellectual as an enlightening and advisory catalyst in the interplay of science, politics, and journalism. The book reflects German, European, and global contemporary history from the mid-20th century to the third decade of the 21st century in a scholarly work and its classification as a testimony to political culture. The Author Dr. Ludger Kühnhardt (1958) is the Director of the Center for European Integration Studies (ZEI) and a Professor of Political Science at the University of Bonn. he translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.